FAKTOR-FAKTOR YANG MEMENGARUHI MANAJEMEN LABA PADA PERUSAHAAN NONKEUANGAN PUBLIK - BINO SULAKSONO (Jurnal Bisnis dan Akuntansi, 2018)
The objective of this research is to analyze factors influencing earnings management on non-financial companies listed in Indonesia Stock Exchange. Those factors are managerial ownership, institutional ownership, profitability, financial leverage, firm size, independent commissioners, board of director, and operating cash flow. Population of this research is non-financial companies which are consistenly listed in Indonesia Stock Exchange from 2013 to 2016. The period of this study is 2014 until 2016. Samples were selected using purposive sampling method, in which only 84 of listed non-financial companies in Indonesia Stock Exchange that meet the sampling criteria, resulting 252 observations used in this research. The hyphotesis tested by using multiple regression method. The empirical findings indicated that profitability, and operating cash flow had influence on earnings management, whereas managerial ownership, institutional ownership, financial leverage, firm size, independent commissioners and board of director had no influence on earnings management.